PROFOUND REDUCTION OF OVARIAN ESTROGEN BY AROMATASE INHIBITION IN OBESE WOMEN - Ross, Lauren A (2014)
OBJECTIVE: We hypothesized that aromatase inhibitor (AI)-induced interruption of estradiol negative feedback would modulate the reproductive hormone profile of obese women. DESIGN AND METHODS: Regularly cycling women aged 18–40 with a BMI of 18–25kg/m2 (normal weight, n=10) or >30kg/m2 (obese; n=12) were given AI daily for 7 days. Urinary hormone profiles were compared between groups. Fourteen eumenorrheic, normal weight women not receiving AI stimulation served as historical controls. Urinary metabolites for LH, FSH, estradiol (E1c), and progesterone (Pdg) were measured and normalized to a 28 day cycle. Serum estrone and estradiol were measured in the late follicular phase. RESULTS: Whole cycle LH, FSH and luteal Pdg excretion did not differ between obese (BMI= 37.1+7kg/m2) and normal weight women treated with AIs, although LH was greater in stimulated compared to unstimulated normal weight women. Whole cycle mean E1c was lower in AI stimulated obese and normal weight participants compared to non-stimulated normal weight controls, but obese women treated with AI excreted far less E1c (467.7±217.4ug/mgCr) than AI-treated normal weight women (911.4±361.8ug/mgCr; P=0.02). Follicular phase serum estrone and estradiol were also lower in AI-treated obese women vs. AI-treated normal weight women (61.7±22.8 and 18.3±3.7 pg/ml, versus 99.1±30.5 and 37.7±5.9 pg/ml, respectively; p=0.034 and 0.005). CONCLUSIONS: Normal gonadotropin output and luteal function occur at the expense of reduced E1c excretion in AI-treated women, and this discrepancy is particularly evident in obese women.